Pemulihan Identitas Naratif Korban Kekerasan Seksual : Sebuah Tinjauan Filsafat dan Teologi Kristen - Jessica Novia Layantara; David Tobing (Reformed Center for Religion and Society, 2021)
As traumatic events, sexual violence can paralyze victim’s identity so that the victim losing her capability as a human being. However , the identity of sexual violence victims could be restored. The question needed to be answered in this article is: What makes it possible, philosophically and theologically, for a victim of sexual violence to be restored or transformed into a redeemed survivor? This article will attempt to answer the question from Paul Ricoeur's view of narrative identity as a framework, and Miroslav Volf's view of sacred memory in the history of salvation as the content of the redeemed survivor identity. The thesis of this article is about the recovery or the changing identity of the victim into a redeemed survivor that is possible through the reestablishment of narrative identity which contains sacred memory in narrative paradigm of Christian salvation history.